Brazilian intelligence at the turning point of 1920/30: encounters and disencounters between writers and educators - Russeff, Ivan (Educar em Revista, 2005)
The absence of a larger number of academic studies which explore therelationship between Literature and Education constitutes one of themotivations for proposing this text; this, because besides the methodologiesfor teaching literature, there is not very much that brings pedagogues andmen of letters together. Thus, Literature and Education will be consideredthrough the broad vision of History, reflecting on the problems whichrefer to Brazilian educational thought and contributing to the criticalunderstanding of the ideas that influenced our culture. In relation to thecharacters in this narrative, the study will be centred on two of the mostexpressive intellectuals of the period: Fernando de Azevedo and Mário deAndrade, whose importance for education and national literature makesfurther presentation unnecessary. As to the period being focused on, knownin our history as the turning point of the years 1920 and 1930, the optionis justified as it constitutes the type of incubator for the germinal ideas ofthe intelligentsia of the country, as will be seen throughout theexposition.